Religious Nationalism in a New Era: A Perspective from Political Islam - Altuntaş, Nezahat (African and Asian studies, 2010)
Abstract Nationalism is an ideology that has taken different forms in different times, locations, and situations. In the 19th century, classical liberal nationalism depended on the ties between the nation state and its citizenship. That form of nationalism was accompanied by “the state- and nation-building” processes in Europe. In the 20th century, nationalism transformed into ethnic nationalism, depending on ideas of common origin; it arose especially after World War I and II and after the collapse of the Soviet Union. Finally, at the beginning of 21st century, nationalism began to integrate with religion as a result of global political changes. The terrorist attack on the United States, and then the effects that the United States and its allies have created in the widespread Muslim geography, have added new and different dimensions to nationalism. The main aim of this study is to investigate the intersection points between religion and nationalism, especially in the case of political Islam.